Contemporary Liver Transplantation : The Successful Liver Transplant Program - Doria, Cataldo (Organ and Tissue Transplantation, 2017)
Contemporary Liver Transplantation provides a comprehensive review of the most crucial and provocative aspects of liver transplantation. It represents a unique source of information and guidance for the current generation of transplant surgeons that evolved from being pure clinicians into savvy administrators knowledgeable in every regulatory aspect governing transplantation. The book contains 35 chapters covering every single aspect of the surgical operation in the donors as well as the recipients of liver transplants. The pre-operative work-up, as well as the post-operative immunosuppression management, and the treatment of recurrent diseases are addressed in detail. Single chapters are dedicated to controversial issues like transplantation in patients diagnosed with NASH, transplantation for patients diagnosed with HCC beyond Milan criteria, and usage of HIV positive donors. Dedicated chapters on HCV, HCC, FHF, and NASH will make this book a unique resource for any health care provider part of the multidisciplinary liver transplant team. The book goes beyond the analysis of the formal medical and surgical aspects of liver transplantation and introduces deep knowledge on key aspects of contemporary transplant programs, such as: physical rehabilitation, palliative care, pregnancy, the multiple requirements of regulatory agencies ruling transplantation, quality measurements for transplant programs, finance and liability. The book is organized in 9 sections focusing on each key aspect of liver transplantation. Contemporary Liver Transplantation addresses the need and the questions of of the multidisciplinary group involved including surgeons, Hepatologists , anesthesiologists, infectious disease specialists, radiologists, transplant coordinators, financial specialists, epidemiologists and administrators.- Resumé vydavatel